202k views
0 votes
3(2x - 1) = 5(x – 6)

User JHoerbst
by
4.4k points

1 Answer

3 votes

Answer:

x = -27

Explanation:

First, distribute the terms outside the parenthesis to each term within:

3(2x - 1) = (2x * 3) + (-1 * 3) = (6x) + (-3) = 6x - 3

5(x - 6) = (x * 5) + (-6 * 5) = (5x) + (-30) = 5x - 30

Isolate the variable. What you do to one side, you do to the other.

6x - 3 = 5x - 30

Add 3 and subtract 5x from both sides:

6x (-5x) - 3 (+3) = 5x (-5x) - 30 (+3)

6x - 5x = -30 + 3

x = -27

x = -27 is your answer.

~

User Jakobhans
by
5.4k points